The Scales for Assessing Emotional Disturbance–Third Edition: Internal Reliability, Interrater Reliability, and Test–Retest Reliability. (November 2021) - Huscroft-D'Angelo, Jacqueline; Wery, Jessica; Martin, Jodie Diane; Pierce, Corey; Crawford, Lindy
The Scales for Assessing Emotional Disturbance–Third Edition Rating Scale (SAED-3 RS; Epstein et al.) is a standardized, norm-referenced measure designed to aid in the identification process by providing useful data to professionals determining eligibility of students with an emotional disturbance (ED). Three studies are reported to address the reliability of the SAED-3 RS. Study 1 investigated the internal reliability of the SAED-3 RS using data from a nationally representative sample of 1, 430 students and 441 with ED. Study 2 examined interrater reliability between 123 pairs of educators who had worked with the student for at least 2 months. Study 3 assessed the test–retest reliability over a 2-week period to determine stability of the SAED-3 RS. Across all studies, scores collected from the SAED-3 RS were determined to be a reliable, stable for measuring the emotional and behavioral functioning of students. Specifically, the averaged coefficient alpha for internal consistency ranged from .79 to .92 for each subscale and .96 for the composite score; interrater reliability coefficients ranged from .77 to .89 for each subscale and .89 for the composite score, and test–retest reliability coefficients ranged from .79 to .92 for each subscale and .96 for the composite score. Limitations, future research and implications for use of the SAED-3 RS are discussed.